IDEOLOGY IN TRANSLATION PROCESS OF NEWS CONTENT IN ENGLISH INTO INDONESIAN: A CASE OF PIKIRAN RAKYAT DAILY NEWSPAPER - Imam Jahrudin Priyanto (University of Kuningan, 2023)
This study aims to reveal another side that is more in-depth than just translation, especially translation in print media. In this regard, the researcher studied translation in one of the leading print media in Indonesia based in Bandung, West Java, namely the Pikiran Rakyat Daily News. The researcher explores ideology in maintaining meaning in the translation of news content in Pikiran Rakyat. This research needs to be done because the translation of international news from English to Indonesian for the sake of print media has many dimensions and problems. The research was conducted using descriptive qualitative methods. There are eleven news of the Pikiran Rakyat examined in this study. The news sourced from foreign news agencies was published in the 2018-2020 range. This research combines two theories, namely translation theory of Newmark and critical discourse analysis (CDA) theory of Van Dijk. Specifically, this study examines ideology and the maintaining of meaning in translating English news content into Indonesian. The results of this study indicate, with the existence of partiality, translation becomes very ideological. This can be seen from the diction, placement of news, and the addition or removal of certain elements in the news. It can be concluded that the translation of international news in Pikiran Rakyat is very ideological. From the linguistic data studied, it appears that Pikiran Rakyat consistently carries the ideology of peace.